USE ENGLISH SONGS AT THE MEDIA TO TEACH LISTENING AND TO IMPROVE STUDENTS ENGLISH LANGUAGE SKILLS IN SMP Negeri 7 Turatea - M, Sumarni (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
Teaching English involves mastering four skills: listening, speaking, reading, and writing. The first skill to be learned is listening, as it is crucial for communication. Listening and speaking are considered the two most essential skills in communication. Therefore, the role of the teacher is crucial in helping students learn to listen. Using songs as a teaching tool can enhance students’ listening skills. Many students are interested and motivated to learn listening through songs. Learning to listen to songs is also beneficial for students’ listening ability and improves their knowledge of new English vocabulary obtained through the songs they listen to.